Horizontal Resource Sharing: A Principal-Agent Approach - Gupta, Anil K. (Institutional Knowledge at Singapore Management University, 1994)
Using a principle-agent modeling approach we examine how career competition between managers of strategic business units (SBUs) interacts with a variety of commission based compensation schemes for inter-SBU resource sharing. We analyze equilibrium behavior in both deterministic and, for the risk averse manager, in stochastic environments.